An infinite servers queue systems with poisson and non poisson arrivals busy period simulation - Ferreira, Manuel Alberto M. (2014)
Many interesting parameters in queue theory study either have not theoretical results or, existing, are mathematically intractable what makes their utility very scarce. In this case a possible issue is to use simulation methods in order to get more useful results. In this paper this procedure is followed to learn something more about quantities of interest for those infinite servers queue systems, in particular about busy period parameters and probability distributions. A fortran program to simulate the operation of infinite servers’ queues is presented in this work. Poisson arrivals processes are considered but not only.